2003
DOI: 10.1073/pnas.2433456100
|View full text |Cite
|
Sign up to set email alerts
|

Cu nanocrystal growth on peptide nanotubes by biomineralization: Size control of Cu nanocrystals by tuning peptide conformation

Abstract: With recent interest in seeking new biologically inspired devicefabrication methods in nanotechnology, a new biological approach was examined to fabricate Cu nanotubes by using sequenced histidine-rich peptide nanotubes as templates. The sequenced histidine-rich peptide molecules were assembled as nanotubes, and the biological recognition of the specific sequence toward Cu lead to efficient Cu coating on the nanotubes. Cu nanocrystals were uniformly coated on the histidine-incorporated nanotubes with high pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(177 citation statements)
references
References 61 publications
1
171
0
5
Order By: Relevance
“…Some recent examples are bolaform mediated synthesis of tailored zeolite nanosheets with improved performance in targeted catalytic reactions (Liu et al, 2014) and templating of mesoporous silicon nanofibers which can be used as anode materials for lithium-ion batteries (Xu et alt., 2014). Furthermore, bolaforms have good interaction properties with several metals such as gold and silver and with their structural support, single-and multi-wall silver particle coated nanotubes (Gao et al, 2005), gold nanocrystals (Djalali et al, 2004) and bionanotubes coated with cupper nanocrystals (Banerjee et al, 2003) can be obtained.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Some recent examples are bolaform mediated synthesis of tailored zeolite nanosheets with improved performance in targeted catalytic reactions (Liu et al, 2014) and templating of mesoporous silicon nanofibers which can be used as anode materials for lithium-ion batteries (Xu et alt., 2014). Furthermore, bolaforms have good interaction properties with several metals such as gold and silver and with their structural support, single-and multi-wall silver particle coated nanotubes (Gao et al, 2005), gold nanocrystals (Djalali et al, 2004) and bionanotubes coated with cupper nanocrystals (Banerjee et al, 2003) can be obtained.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39] In a few cases, the applicable enzymes themselves catalyze biomineralization reactions, which result in their self-immobilization and retention of activity within the inorganic matrix without addition of a separate biomineralizing peptide. 40,41 Whether part of a physiological function or of man-made design, many peptides that catalyze biomineralization reactions (e.g., histidine-rich proteins, [42][43][44] noble metal nanoparticle-forming peptides, 45,46 silaffins, silicatiens, and other lysine-rich proteins 47 ) have an overall positive charge and are amphiphilic in nature; characteristics that are also shared with many AMPs. Overlapping traits such as these could be exploited in designing AMPs that mediate their own immobilization, thereby enhancing their effectiveness through increased stability and protection from inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the porosity changes of the porous polysiloxane induced by the introduction of notrophenyl groups, we measured the surface area and pore volumes of modified silicas (SiNH 2 ), (Si-o-NO 2 ), (Si-m-NO 2 ) and (Si-p-NO 2 ) with nitrogen adsorption-desorption isotherms (BET) (Figure 4) and Barrett-Joyner-Halenda (BJH) pore diameters methods [27,28]. On the other hand, we observed that SiNH 2 has a decrease BET surface area as additional groups' immobilization takes place to give 241 m 2 /g and a pore volume of 0.67 cm 3 /g.…”
Section: Surface Propertiesmentioning
confidence: 99%